'Elgin‐ND' Spring Wheat: A Newly Adapted Cultivar to the North‐Central Plains of the United States with High Agronomic and Quality Performance. Issue 2 (15th April 2016) - Mergoum, Mohamed; Simsek, Senay; Zhong, Shaobin; Acevedo, Maricelis; Friesen, Timothy L.; Alamri, Mohammed S.; Xu, Steven; Liu, Zhaohui
Abstract : The spring wheat ( Triticum aestivum L.) industry and growers usually value adapted wheat cultivars with high quality attributes, an essential criteria for maintaining wheat as a competitive commodity at the national and international levels. Therefore, the goal of the breeding program is to develop wheat cultivars that meet the above criteria using appropriate breeding tools. 'Elgin‐ND' (CV‐1116, PI 668099), a hard red spring wheat (HRSW) developed at North Dakota State University was released by the North Dakota Agricultural Experiment Station in 2013. Elgin‐ND, tested as experimental line ND818, was released because it is adapted to the US spring wheat growing conditions. It combines high yield potential with high protein and end‐use quality and has a good disease resistance package. This includes resistance to Fusarium head blight [caused by Fusarium graminearum Schwabe; teleomorph Gibberella zeae (Schwein.) Petch)]; leaf diseases including stem rust (caused by Puccinia graminis Pers.:Pers. f. sp. t ritici Eriks. & E. Henn) and leaf rust (caused by Puccinia triticina Eriks.); tan spot [caused by Pyrenophora tritici‐repentis (Died.) Drechs]; and bacterial leaf blight (caused by Xanthomonas translucens pv. undulosa ). However, Elgin‐ND relies heavily on the major Lr21 gene that confers resistance to leaf rust. Thus, it is susceptible to the new race that overcomes the Lr21 gene. The name Elgin‐ND was chosen for ND818 after a small town in western North Dakota, where the cultivar is expected to be widely planted.